REDUCING EATING DISORDERS THROUGH EXPERIENTIAL PSYCHOTHERAPY: A CASE STUDY OF ANOREXIA NERVOSA - CARANFIL Narcisa Gianina (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Over the last decades, the prevalence of eating disorders has increased dramatically. In the current psychiatric nomenclature of the DSM-5 [2], the eating disorders consist of three clearly defined syndromes, i.e. anorexia nervosa, bulimia nervos and binge-eating disorder. The onset of the most clinical cases occurs in adolescence or young adulthood. Data provided by psychiatric practice reveal that eating disorders occur more frequently in women, compared with men. These disorders appear to be multidetermined. Thus, the risk for (or protection against) the development of eating disorders resides in several factors, i.e. genetic, neurohormonal, family, psychological and sociocultural. Negative life events can also play a triggering role. Anorexia nervosa is a debilitating mental disorder with profound biological, psychological and social consequences. Although the overall incidence rate of anorexia nervosa is considerably stable over the past decades, the incidence among adolescents has increased. Different types of psychotherapeutic interventions (e.g., family-based therapy, cognitive-behavioral therapy, dialectical behavior therapy, interpersonal therapy, etc.) are used to treat eating disorders. However, the benefits of experiential techniques (e.g., emotion-focused therapy or gestalt therapy) have been less explored. This paper focuses on a 19-yearold adolescent girl presenting with symptoms of anorexia nervosa. The complaints, results of the initial assessment, goals of the therapeutic sessions, working techniques as well as gains of the intervention based on experiential methods (e.g., the empty chair technique, metapositions, cognitive reframing, etc.) are reviewed. Practical implications are discussed considering the potential of experiential psychotherapy in assisting clients with eating disorders.